Kecerdasan Buatan dan Transformasi Digital Kewirausahaan: Pemetaan Sistematis melalui Pendekatan Bibliometrik Tren dan Penelitian Masa Depan - Yan Aditiya Pratama; Stefanus Rumangkit (Jurnal Bisnis Darmajaya, 2025)
The purpose of this study is to map current and future research on the topic of AI and entrepreneurship. The approach of this study is bibliometric, with secondary data as the data source. The processed articles are 34 articles with published articles in reputable national journals (SCOPUS), where the topics in the articles are business, management, and accounting. The results of the study show that there are nine clusters that are mapped in AI and entrepreneurship research, namely Cluster # 1 shows a focus on advanced technology and data analysis in business innovation, Cluster # 2 relates to industrial innovation and digital transformation in various sectors, Cluster # 3 covers efficiency and desire in multiple sectors through environmental technology and innovation, Cluster # 4 focuses on the development of business models and health technology, as well as innovation in patents and startups, Cluster # 5 focuses on entrepreneurial action and environmental economics, as well as sustainable development, Cluster # 6 relates to business development and entrepreneurial ecosystems through effective decision making, Cluster # 7 emphasizes entrepreneurship education and artificial intelligence-based technological innovation, Cluster # 8 focuses on digital entrepreneurship and digital transformation through a lean startup approach, and Cluster # 9 relates to entrepreneurial skills and risk management in a dynamic business environment.